Ask Question
31 August, 01:58

F (x) = -3x-2 find f (3)

+2
Answers (1)
  1. 31 August, 03:28
    0
    f (3) = - 11

    Step-by-step explanation:

    f (x) = - 3x-2

    let x=3 and replace it in the above equation

    f (3) = - 3 (3) - 2

    f (3) = - 9 - 2

    f (3) = - 11
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “F (x) = -3x-2 find f (3) ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers